Avoiding New Biopsies by Identification of IDH1 and TERT Promoter Mutation in Nondiagnostic Biopsies From Glioma Patients. Issue 4 (28th February 2020) - Barritault, Marc; Picart, Thiébaud; Poncet, Delphine; Fenouil, Tanguy; d'Hombres, Anne; Gabut, Mathieu; Guyotat, Jacques; Jouanneau, Emmanuel; Ameli, Roxana; Joubert, Bastien; Streichenberger, Nathalie; Vasiljevic, Alexandre; et al.
Abstract: BACKGROUND: Biopsies in patients with a suspected glioma are occasionally nondiagnostic. OBJECTIVE: To explore the utility of molecular testing in this setting by determining whether IDH1 and TERT promoter (pTERT) mutations could be detected in nondiagnostic biopsies from glioma patients. METHODS: Using SNaPshot polymerase chain reaction, we retrospectively assessed IDH1 and pTERT mutation status in nondiagnostic biopsies from 28 glioma patients. RESULTS: The nondiagnostic biopsy (needle biopsy n = 25, open or endoscopic biopsy n = 3) consisted of slight glial cell hypercellularity, hemorrhage, and/or necrosis. After another biopsy (n = 23) or a subsequent surgical resection (n = 5) the diagnosis was an IDH1 -wildtype (WT) pTERT-mutant glioma (glioblastoma n = 16, astrocytoma n = 4), an IDH1 -mutant pTERT-mutant oligodendroglioma (n = 1), an IDH1 -mutant pTERT-WT astrocytoma (n = 1), and an IDH1 -WT pTERT-WT glioblastoma (n = 6). An IDH1 mutation was identified in the nondiagnostic biopsies of the 2 IDH-mutant gliomas, and a pTERT mutation in the nondiagnostic biopsies of 16 out of the 21 of pTERT mutant-gliomas (76%). Overall, an IDH1 and/or a pTERT mutation were detected in 17 out of 28 (61%) of nondiagnostic biopsies. Retrospective analysis of the nondiagnostic biopsies based on these results and on imaging characteristics suggested that a new biopsy could have been avoided in 6 patients in whom a diagnosis of "molecular glioblastoma" could have been done with a high level of confidence. CONCLUSION: In the present series, IDH1 and pTERT mutations could be detected in a high proportion of nondiagnostic biopsies from glioma patients. Molecular testing may facilitate the interpretation of nondiagnostic biopsies in patients with a suspected glioma.